PENGARUH LIKUIDITAS, SOLVABILITAS DAN RASIO AKTIVITAS TERHADAP PROFITABILITAS PT. MEDIA NUSANTARA CITRA TBK. PERIODE 2011-2020 - Ida Yusnita (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
This study aims to determine the effect of Liquidity, Solvency, and Activity Ratio on Profitability of Pt. Media Nusantara Citra Tbk. In 2011-2020, partially and simultaneously, this study explains the factors that affect profitability. These factors are the influence of Liquidity, Solvency, and Activity Ratio. The data used in this study is secondary data, namely Summary of Financial Statement data obtained from the financial statements of PT. Unilever Indonesia Tbk. Listed on the Indonesia Stock Exchange 2011-2020. Based on the results of data analysis that has been carried out on all data obtained, it can be concluded as follows: 1) Liquidity has no partial and insignificant effect. It is proven by the value of tcount < ttable (0.396 < 2,447) with a value of sig = 0.706 > 0.05 so that hypothesis I cannot be accepted. 2) Solvency has no partial and insignificant effect. It is proven by the value of tcount < ttable (-1.562 < -2.447) with a value of sig = 0.169 > 0.05 so that hypothesis II cannot be accepted. 3) Activities have a partial and significant effect on profitability. It is proven by the value of tcount > ttable (6.398 > 2,447) with a value of sig =0.001 <0.05 so that the third hypothesis can be accepted. 4) Liquidity, Solvency, and Activity have a simultaneous effect on Profitability, as evidenced by the value of Fcount > Ftable or 19.656 > 4.76, and with a significant value of 0.002 < 0.05 so that hypothesis IV can be accepted. 5) The magnitude of the influence of each The independent variables on the dependent variable are Liquidity, Solvency and Activity on Profitability at PT. Media Nusantara Citra Tbk. The 2011-2020 period is 90.8%. While the rest (100%-90.8%) which is equal to 9.2% is influenced by other variables not examined in this study